PROTOKOL KESEHATAN DAN GENEALOGI HUKUM DI MASA PANDEMI COVID-19 - Citrawan, Harison (Veritas et Justitia, 2022)
This article encapsulates the dialectics between law and science in the time of Covid-19 pandemic. It attempts to appraise the objectivity and normativity of the Health Protocol by rendering both legal and scientific characteristics. As a legal construct, the Protocol is genealogically justified from three discursive aspects of: its position between law and science, its reflection on matter and the materiality of law, and the immanent power within it. A close scrutiny towards the Protocol enables us to grasp legal objectivity and normativity not to be seen as a traditional one-way linear trajectory. In lieu, the force of law derives from plural-micro processes insisting a democratic process of knowledge in it.